What Constrains Liquidity Provision? Evidence from Institutional Trades. (9th July 2020) - Çötelioğlu, Efe; Franzoni, Francesco; Plazzi, Alberto
Abstract: The article studies liquidity provision by institutional investors using trade-level data. We find that hedge fund trades are a more important predictor of stock-level liquidity than mutual fund trades. However, hedge funds' liquidity provision is more exposed to financial conditions than that of mutual funds. Hedge funds that are more constrained in terms of leverage, age, asset illiquidity, and past performance exhibit a stronger shift toward liquidity consumption when funding condition tighten. Stocks with more exposure to constrained liquidity providing hedge funds suffered more during the financial crisis.